Customer Lived Experiences Of Proactive Social Media Engagement And Its Influence On Brand Equity: An IPA Approach - Wiwin Riski Windarsari; Betania Kartika Muflih (International Journal of Education Management and Religion, 2026)
This study examines how proactive social media engagement, conducted through the Social Customer Relationship Management (Social CRM) practices of Scarlett Whitening, influences customer perceptions of brand meaning and overall brand equity. As brands increasingly initiate unsolicited interactions on Instagram and TikTok, understanding how customers interpret these engagements becomes essential for explaining their emotional and behavioral responses. Using a qualitative design, this research employs Interpretative Phenomenological Analysis (IPA) to explore customers’ lived experiences and the meanings they assign to proactive brand interactions. The population of the study includes active social media users in Indonesia who follow beauty brands. A homogeneous purposive sample of six participants aged 19–30 years was selected based on their direct experience receiving proactive engagement from Scarlett Whitening. Data were collected through semi-structured in-depth interviews as the primary instrument, complemented by field notes to support interpretive rigor. The findings reveal three key themes: feeling seen and recognized by the brand, reinterpreting brand intentions, and shifts in attitudes and behavioral loyalty. Participants reported emotional validation, increased trust, and stronger relational connection, which subsequently enhanced their willingness to purchase and advocate for the brand. These results demonstrate that proactive Social CRM operates as a relational experience that strengthens customer–brand bonds and contributes to experience-driven brand equity.